2006
DOI: 10.1055/s-2006-931803
|View full text |Cite
|
Sign up to set email alerts
|

From Concept to Practice: The Recent History of Preterm Delivery Prevention. Part II: Subclinical Infection and Hormonal Effects

Abstract: Under the new cervical insufficiency postulate, the final common pathway theoretically may be influenced by multiple interventions including not only cerclage, but also antibiotics, anti-inflammatory drugs, or progesterone. Since the late 1970s, accumulating evidence has implicated intrauterine infection as a cause of preterm labor. The use of antimicrobial therapy for the prevention of preterm delivery (PTD), although plausible and appealing, has remained largely ineffective so far. A decade of antimicrobial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 74 publications
0
12
0
4
Order By: Relevance
“…However, the lack of benefits from antimicrobial therapy during pregnancy in the prevention of preterm delivery suggests a more complex picture (56). Indeed, studies have found that the presence of intrauterine bacteria alone is not sufficient (50); rather, a combination of microbes and microbial products that trigger the activation of the innate immune system and the production of proinflammatory cytokines, prostaglandins, inflammatory mediators, and matrix-degrading enzymes ultimately leads to preterm births (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the lack of benefits from antimicrobial therapy during pregnancy in the prevention of preterm delivery suggests a more complex picture (56). Indeed, studies have found that the presence of intrauterine bacteria alone is not sufficient (50); rather, a combination of microbes and microbial products that trigger the activation of the innate immune system and the production of proinflammatory cytokines, prostaglandins, inflammatory mediators, and matrix-degrading enzymes ultimately leads to preterm births (22).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, effective anti-intrauterine infection mechanisms are important in maintaining a viable pregnancy. However, the use of antimicrobial therapy for the prevention of preterm delivery has remained ineffective, begging for better understanding of the molecular mechanisms of the immune regulation at the maternofetal interface (56). On the other hand, pregnancy also presents a major challenge to the maternal immune system, due to the existence of paternal alloantigens in the fetus that are foreign to the mother.…”
mentioning
confidence: 99%
“…During pregnancy, total cervical collagen content increases to provide strength to the cervix (Harkness and Nightingale 1962; Goilichkowski et al 1980; Kokenyesi and Woessner 1990; Eckman et al 1991; Woessner and Kokenyesi 1991; Yu and Leppert 1991). Before the onset of labor contractions and over a period of weeks, the cervix remodels through a process of collagen disorganization (Weiss 2000; House and Socrate 2006; Vidaeff and Ramin 2006a; Vidaeff and Ramin 2006b) wherein water content and proteoglycans are increased, and collagen concentration is decreased (Danforth et al 1960; Goilichkowski et al 1980; Yu and Leppert 1991; Leppert et al 2000; Feltovich et al 2005; McFarlin et al 2006), thus resulting in increased extensibility and reduced stiffness of the cervix. During this process, increased space results among the collagen fibrils (Leppert and Yu 1991; Leppert 1995; Leppert et al 2000; Feltovich et al 2005; Clark et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Release of prostaglandins and other inflammatory mediators contribute to the development of preterm labor, providing a plausible explanation for the link between intrauterine infection and preterm delivery. 23,25 …”
Section: Infection and Preterm Birthmentioning
confidence: 99%